Aplikasi Composite Hanging Breakwater Sebagai Pelindung Kolam Pelabuhan Bantaeng - Chairul Paotonan; Hasdinar Umar; Sabaruddin Rahman; Achmad Yasir Baeda; Muhammad Arsyad Thaha; Wasir Samad; Muhammad Aksar (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Bantaeng Port already has a dock for the loading and unloading goods and passengers. The problem is, the port cannot be operated optimally because of the large wave height at the dock so that the loading and unloading process is not optimal. The Bantaeng Port Master Plan document recommends the construction of a breakwater. One type of breakwater that can be applied is hanging breakwater. This study analyzes the dimensions of hanging breakwater based on environmental data. The study began by collecting data on deep-sea waves and related documents. Deep sea waves are analyzed to obtain wave parameters at the building site. This structure will be placed at a depth of 20 m. After the wave parameters at the location of the structure are known, then calculate the transmission coefficient using the equation developed by previous researchers [2]. The transmition coefficient is further used to calculate the wave behind the structure. The wave behind the structure must be smaller or equal to the required wave height [3]. The results obtained shows that the higher the wave in front of the building is Hi = 1.79 m, the wave height behind the structure is required is Ht = 0.7 m and the transmission coefficient is Kt = 0.8. The width of the building in the direction of wave propagation can be calculated using the equation L= 46.757e-0.08D.